Miracle on 133rd Street - Manzano, Sonia (Atheneum Books for Young Readers, 2015)
The day before Christmas, everyone in Jose's neighborhood seems grumpy, including his mother who is homesick for Puerto Rico, but when he and his parents return from the pizzeria where they borrowed an oven to cook their roast, the heavenly aroma reminds those they pass of all they have to celebrate.